2004
DOI: 10.1016/j.fertnstert.2003.11.048
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of apoptosis and proliferation in endometriosis

Abstract: Objective: To evaluate whether endometriosis could be related to an impaired balance between apoptosis and proliferation, two processes which could be modulated by hormonal status.Design: Immunohistochemical study.Setting: Academic research laboratory. Intervention(s):Endometriotic samples obtained from peritoneum of women aged 26-40 years who were undergoing laparoscopy for pain or infertility. Main Outcome Measure(s):Apoptotic cells were detected with the use of the terminal deoxynucleotidyl transferase-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(105 citation statements)
references
References 37 publications
2
98
0
2
Order By: Relevance
“…These results in mice are in accord with previous findings of reduced PR expression in human endometriosis. 11,25,26 We also observed that FKBP52 levels were reduced in ectopic lesions of WT-WT samples with only a few stromal cells showing expression ( Figure 4B …”
Section: Pr and Fkbp52 But Not Er␣ Expression Is Reduced In Mouse Ementioning
confidence: 60%
See 1 more Smart Citation
“…These results in mice are in accord with previous findings of reduced PR expression in human endometriosis. 11,25,26 We also observed that FKBP52 levels were reduced in ectopic lesions of WT-WT samples with only a few stromal cells showing expression ( Figure 4B …”
Section: Pr and Fkbp52 But Not Er␣ Expression Is Reduced In Mouse Ementioning
confidence: 60%
“…In fact, the pattern of cell proliferation in ectopic lesions differs from estrogen-and P 4 -governed proliferation of eutopic endometria. 25,26 The proliferative status of mouse ectopic lesions due to FKBP52 deficiency was assessed by Ki-67 immunohistochemistry. For Ki-67 quantification, five high-powered fields per respective section were analyzed microscopically.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Accumulated evidence indicates that decreased apoptosis of endometrial cells in a phase-dependent manner during the menstrual cycle may facilitate ectopic survival of implanted endometrial fragments (Dmowski et al 2001, Garcia-Velasco & Arici 2003. In healthy women, the endometrium that is refluxed into the peritoneum undergoes apoptosis called anoikis because of its failure to interact with the extracellular matrix required for the growth of ectopic endometrium (Béliard et al 2004). The resistance of endometrial cells to apoptosis and their increased sensitivity to proliferation is one of the proposed theories for the development of endometriosis (Harada et al 2004).…”
Section: R202 L Pirdel and M Pirdelmentioning
confidence: 99%
“…Endometriosis is a pathologic condition that involves abnormal endometrial cell adhesion, growth, and proliferation in ectopic tissues, such as the ovary and the peritoneal surface (Béliard et al, 2004). Studies of p53 codon 72 polymorphism with respect to the incidence of endometriosis have been controversial.…”
Section: Discussionmentioning
confidence: 99%